Estudios Limnológicos en la Cuenca del Riachuelo (Corrientes, Argentina). V. Biota acuática de los "embalsados" de la Laguna Brava y caracteres del hábitat - Varela, María E.; Corrales, Marta Angélica; Tell, Guillermo; Poi de Neiff, Alicia; Neiff, Juan J. (Ecosur, 2024)
La Brava pond, a shallow water body belonging to the Riachuelo Basin, is surronded by a wide and dense belt of aquatic macrophytes, composed mainly by Typha latifolia, T. angustifolia, Fuirena robusta forming by the tight intermixing of the roots and the progressive accumulation of detritus true floating island, called “embalsados”. This “embalsados” are of different extention, development and complexity, having in general a marginal ubication because of the wind action among them are defined little water bodies as well as on their very irregular surface, with some particular limnological characteristics. Althought the “embalsados” have equivalent vegetal formations in the tropical and subtropical world regions, the information concerning to the biota inhabiting the little water bodies formed among them or in their surface, are very poor. In this paper are described the algae and invertebrate fauna of the “embalsados” pools of “La Brava” pond, giving data of the relative abundance in relation with the more important limnological feature, in order to compare their structure with the biotic communities corresponding to the central area of the pond.